THE APPLICATION OF CEC RATIO METHOD IN THE EVALUATION OF TUFFACEOUS SANDSTONE RESERVOIRS: AN EXAMPLE IN THE X DEPRESSION OF THE HAILAR‐TAMTSAG BASIN. Issue 4 (July 2016) - Bao‐Zhi, PAN; Si‐Hui, LIU; Bu‐Zhou, HUANG; Chun‐Hui, FANG; Yu‐Hang, GUO
Abstract: The logging evaluations of tuffaceous sandstone reservoirs are always difficult problems. The existence of tuff results in the great variations in reservoir pore structures, and the associated physical properties, which greatly influence the formation parameters. Therefore, the effects of tuff on saturation models cannot be ignored. This study took the tuffaceous sandstone reservoirs in the X depression of the Hailar‐Tamtsag Basin as an example. Based on the differences of the response characteristics between the tuff and shale, the component content was calculated using a method which combined a bacterial foraging algorithm and a particle swarm optimization algorithm. The experimental data of the cation exchange capacity (CEC) proved that the tuff had conductivity. Then, the resistivity of the tuff was obtained using the relationship between the CEC and the resistivity, which was then used to calculate the saturation. Finally, a new method was proposed to calculate the saturation of a tuffaceous sandstone reservoir, and was referred to as a CEC ratio method. The calculation results of this method were found to have a good application effect.